Between Marx and Coca-Cola : youth cultures in changing European societies, 1960-1980 - Schildt, Axel; Siegfried, Detlef (Berghahn Books, 2006)
In the 1960s and 70s, a new youth consciousness emerged in Western Europe which gave this period its distinct character. This volume demonstrates how international developments fused with national traditions, producing specific youth cultures that becameleading trendsetters of emergent post-industrial Western societies.